STRATEGI BERSAING PASAR LEGI KOTA SURAKARTA DALAM MENGHADAPI PASAR MODERN - mohamad harisudin (Universitas Muhammadiyah Yogyakarta, 2019)
The presence of modern markets in Surakarta city is accepted by its resident, this can be seen from the increasing number of modern markets in recent year. Modern market consumers have taken a portion of traditional market consumers. This situation needs to be anticipated by traditional market managers in the form of competitive strategies. The purpose of this study was to determine the strengths, weaknesses, opportunities and threats factors that affect the development and the strategies used in developing Pasar Legi toward the presence of modern market. The basic method of this research was descriptive analysis. Data collection methods was done by interviewing, observing and recording techniques. Key informants were selected purposively based on the quality of information, which consists of the manager of Pasar Legi, market traders and consumers/buyers in this traditional market. The market was chosen purposively according to the research objectives, namely Pasar Legi Surakarta City. Data analysis method used analysis of Grand Strategy Matrix, SWOT Matrix, and QSPM from Fred R. David. The results showed that the strategic position of Pasar Legi was in quadrant I, which was a combination of strength and opportunity. The most priority strategy by the manager of Pasar Legi to face of the existence of the modern market is to build a good service system between market traders and consumers.